2022
DOI: 10.3390/ma15051828
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Element and Sensitivity Analysis of Anisotropic Thermoelastic Metal and Alloy Discs with Holes

Abstract: The main aim of this paper was to develop an advanced processing method for analyzing of anisotropic thermoelastic metal and alloy discs with holes. In the boundary element method (BEM), the heat impact is expressed as an additional volume integral in the corresponding boundary integral equation. Any attempt to integrate it directly will necessitate domain discretization, which will eliminate the BEM’s most distinguishing feature of boundary discretization. This additional volume integral can be transformed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The internal stress is given by [ 22 ] where represents the initial stress derived from the initial strain. Additionally, and in Equation (36) can be expressed as [ 1 , 11 ] …”
Section: Bem Implementation For the Elastoplastic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The internal stress is given by [ 22 ] where represents the initial stress derived from the initial strain. Additionally, and in Equation (36) can be expressed as [ 1 , 11 ] …”
Section: Bem Implementation For the Elastoplastic Fieldmentioning
confidence: 99%
“…Iij (p) represents the initial stress derived from the initial strain. Additionally, S kij (p, q) and σ [1] ijks (p, q) in Equation ( 36) can be expressed as [1,11]…”
Section: Bem Implementation For the Elastoplastic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…When using two-temperature thermoelasticity with relaxation durations to study a variety of issues, Youssef and El-Bary [31] found that the outcomes are qualitatively distinct from those obtained when using one-temperature thermoelasticity. Fahmy et al [32][33][34][35][36] studied the boundary element modeling and fractional boundary element solution of ultrasonic wave propagation according to the magneto-thermoviscoelastic medium in the context of the nonlinear generalized photothermal.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the BEM impose restrictions on the ability of handling the exterior acoustic problem in nonisotropic and nonhomogeneous media. In these cases, a novel singular boundary method (SBM) 25,26 was proposed to handle the acoustic problems while Fahmy et al [27][28][29][30][31][32][33][34][35] optimized the algorithm to reduce the computational complexity and computational time and to overcome some nonlinear problems. These methods contribute to solving singular or hypersingular integrals, but much of the research is focused on future-proofing the method and higher resolutions of elements is continually desired, particularly as this is necessary for modeling high frequency problems.…”
Section: Introductionmentioning
confidence: 99%